The GLE #73 on 28 October 2021: spectra, angular distribution and terrestrial effects - Mishev, Alexander; Kocharov, Leon; Koldobskiy, Sergey; Larsen, Nicholas; Riihonen, Esa; Vainio, Rami; Usoskin, Ilya (2023)
The first solar proton event observed at ground, that is ground level enhancement, of solar cycle 25 was detected on 28 October 2021 by several neutron monitors (NMs), specifically those in the polar region as well as by space-borne instruments. It was identified as the GLE (ground-level enhancement) #73 in the International GLE database. The strongest signal at the ground was registered by the DOMC/DOMB monitors located at the Antarctic plateau at the Concordia French-Italian research station. Here, we report the observations and the study of this event using the global NM network and SOHO/ERNE records. We present the derived angular and spectral characteristics of solar energetic protons, including their dynamical evolution throughout the event. Several applications are discussed, namely the terrestrial effects of the GLE particles during the event.